Nitroxin bio-fertilizer improves growth parameters, physiological and biochemical attributes of cantaloupe (Cucumis melo L.) under water stress conditions - Abdolhamid Zahedyan; Abdolhossein Aboutalebi Jahromi; Abdolrasool Zakerin; Vahid Abdossi; Ali Mohammadi Torkashvand (Journal of the Saudi Society of Agricultural Sciences)
Effect of chemical- and bio-fertilizers (Nitroxin) on growth parameters, physiological and biochemical attributes, and yield of cantaloupe (Cucumis melo L.) under water stress conditions has been studied. Irrigation was done at 3 levels including 50, 75, and 100% of the water requirement of the cantaloupe plant. Water stress had an adverse effect on plant growth and the application of 120 kg ha−1 chemical fertilizer with Nitroxin in 100% water requirement had the highest growth parameters including fruit weight (1.84 kg) and fruit length (20.71 cm). The highest Malondialdehyde content was observed at 60 kg ha−1 of chemical fertilizer using Nitroxin. Application of Nitroxin had a significant effect on electrolyte leakage, proline content, relative water content, colour, vitamin C, titratable acidity, firmness, and total soluble solids (TSS) during water stress. The highest content of total chlorophyll (5.81 mg g−1 fresh weight) was observed at 100% field capacity with 180 kg ha−1 of chemical fertilizer with Nitroxin. The total phenol content of fruit enhanced by increasing drought stress and a significant difference was observed by application of biological and chemical fertilizers compared to control. Antioxidant enzyme activity including ascorbate peroxidase, catalase, superoxide dismutase and peroxidase increased during water stress and the application of chemical fertilizer with Nitroxin enhanced antioxidant enzyme activity during stress. Overall, the application of chemical fertilizers and Nitroxin improved growth parameters, physiological and biochemical attributes and yield of cantaloupe plants during water stress.